[OA148] A multi-center dosimetry study to evaluate imaging dose from Elekta XVI and varian OBI KV-CONE beam CT systems to cardiovascular implantable electronic devices (CIEDS). (August 2018) - Aslian, Hossein; Delana, Anna; kaiser, Stefano Ren; Moretti, Eugenia; Foti, Claudio; Bregant, Paola; Denaro, Mario De; Longo, Francesco; Severgnini, Mara
Abstract : Purpose: By increasing the use of daily CBCT, additional delivered imaging dose to the patient became a matter of concern. This can also raise concerns about patients with CIEDs since accumulated dose to these devices highly needs to be limited. The aim of this study is to investigate the imaging dose to the CIEDs from Elekta XVI and Varian OBI kV-CBCT systems performed by a multi-institutional study. Methods: Four geographically separated centers with different CBCT imaging systems and three different dosimetric measurement methods including Gafchromic films, metal-oxide-semiconductor field-effect transistor (MOSFET) and thermoluminescence dosimeters (TLDs) participated in this multi-center study. At each center an anthropomorphic phantom (Alderson RANDO phantom) was used and the CIED was placed in the alderson's left clavicular region using the same setup. The dosimeter was fixed on top of the device over which a 1-cm thick bolus was used to simulate patient's skin. Different standard CBCT-imaging protocols which are commonly used in clinical practice of each center were applied namely, Head&Neck (HN), Chest, Thorax, Symmetry, Prostate and Pelvis. Results: The maximum values of imaging doses were found once CIEDs were inside the CBCT field. They were between the following values: HNS20 (XVI):2.57 mGy/100 mAs, Thorax (OBI):2.92 mGy/100 mAs, ChestM15-left (XVI): 1.52 mGy/100 mAs, Symmetry-left (XVI): 5.67 mGy/100 mAs. However, they received much lower dose once the CIEDs were not inside the field. Conclusion: This study shows that although imaging doses received by CIEDs outside the CBCT field is negligible, a special attention should be paid to this value when CIEDs are inside the CBCT field because daily use of CBCT can make a considerable contribution to the total dose received by CIED. Based on the obtained results, it is possible that in some protocol like symmetry total imaging dose to CIED in a 30-fraction reach as high as 50 cGy. Therefore in such cases, this additional imaging dose should not be ignored when classifying CIED patients into risk groups.